2018
DOI: 10.1017/s136672891800041x
|View full text |Cite
|
Sign up to set email alerts
|

Novel-word learning, executive control and working memory: A bilingual advantage

Abstract: Studies of the effects of bilingualism on cognition have given results that do not consistently replicate, reflecting at least in part wide differences in criteria for bilingualism and heterogeneity of language combinations within studied samples. We examined the bilingual advantage in attention, working memory and novel-word learning in early sequential Hindi–English bilinguals. We sought to clarify the aspects of cognition that benefit from bilingualism by using multiple measures and a sample sufficiently we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 101 publications
(156 reference statements)
1
23
0
Order By: Relevance
“…For these two studies, although their overall conclusion was bilingual individuals were at advantage, not every single task supported this conclusion. For instance, in the task of Listening Recall (in Warmington et al (2018)'s study), the bilingual group did not significantly outperform the monolingual group. By comparing the measurement of WM in these studies, it is indicated that verbal WM has received the most controversy in the investigation of bilingual advantage.…”
Section: Working Memory Measurementmentioning
confidence: 73%
See 2 more Smart Citations
“…For these two studies, although their overall conclusion was bilingual individuals were at advantage, not every single task supported this conclusion. For instance, in the task of Listening Recall (in Warmington et al (2018)'s study), the bilingual group did not significantly outperform the monolingual group. By comparing the measurement of WM in these studies, it is indicated that verbal WM has received the most controversy in the investigation of bilingual advantage.…”
Section: Working Memory Measurementmentioning
confidence: 73%
“…5) The study had a clear presentation of methodology design, including the type of tasks used to measure participants' working memory, and a targeted (or at least relevant) linguistic development aspect to be measured (such as working memory in relation to novel word learning, as in (Singh et al, 2018;Warmington, Kandru-Pothineni, & Hitch, 2018).…”
Section: Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Bialystok, 1988, 2007, 2008; Costa, Hernandez, & Sebastian-Galles, 2008) to recent articles (e.g. Padilla et al, 2016; Warmington, Kandru-Pothineni, & Hitch, 2019) on bilingual advantage. Yet there were many individual variations that might affect the bilingual advantages for cognition; for instance, their education, immigration status and social economic status (van den Noort, Struys, & Bosch, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…However, in the context of recent challenges to theory, concerns about methods and the appropriateness of statistical analyses employed in bilingual cognition research [2], the question of whether or not bilingualism is associated with enhanced cognitive abilities remains fiercely debated. One theme that has emerged is that if a bilingual advantage does exist, it may be task-specific or otherwise operate only across particular groups of participants [19,20]. Crucially, it may also be premature to speak of a universal bilingual advantage in non-verbal cognitive functioning in light of a recent report of a bilingual disadvantage in metacognition [21].…”
Section: Introductionmentioning
confidence: 99%